Predictors of Residual Viremia in Patients on Long-term Suppressive Antiretroviral Therapy - Zheng, Lu (2012)
BACKGROUND: HIV-1-infected individuals with plasma RNA <50 copies/mL on antiretroviral therapy (ART) may have residual, low-level viremia detectable by PCR assays which can detect a single copy of viral RNA (single-copy assay, SCA). The clinical predictors of residual viremia in patients on long-term suppressive ART are incompletely understood. METHODS: We evaluated factors associated with residual viremia in patients on suppressive ART who underwent screening for a raltegravir intensification trial (ACTG A5244). The screened population was HIV-1-infected adults receiving ART for ≥12 months with pre-ART HIV-1 RNA >100,000 copies/mL and on-therapy RNA levels below detection limits of commercial assays for ≥6 months. RESULTS: Of 103 patients eligible for analysis, the median age was 46 years and the median duration of viral suppression was 4.8 years. Sixty-two percent had detectable viremia (>0.2 copies/mL) by SCA (median 0.2 copies/mL; quartile [Q] 1, Q3 [<0.2, 1.8]). Younger patients had lower HIV-1 RNA levels than older individuals (r=0.27, p=0.005). Patients with virologic suppression on ART for 2 years or less had higher residual viremia than those with suppression for more than 2 years (median 2.3 vs. 0.2 copies/mL, p=0.016). CONCLUSIONS: Among HIV-1-infected patients with pre-ART HIV-1 RNA >100,000 copies/mL, residual viremia was detectable in the majority (62%) despite many years of suppressive ART. Higher level viremia was associated with older age and less than 2 years of virologic suppression on ART. These findings should help in selection of candidates for clinical trials of interventions designed to eliminate residual viremia.